2012
DOI: 10.1111/j.1526-100x.2011.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation, Moisture Content and Germination of Zostera marina L. Seed

Abstract: Zostera marina is the only seagrass species whose seeds have been successfully used in large-scale restoration. Although progress has been made in refining Z. marina restoration protocols, additional information on Z. marina seed physiology is necessary as the science of seagrass restoration evolves. We tested the germination rates of Z. marina seeds under different relative humidities and temperatures for different periods of time. Z. marina seed moisture content (MC) and germination rates were also tested wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…However, seagrass may have been transported on ships via ballast (in rocks or sand), as mattress material or in anchor wells. Shipping time from SE Australia to Chile (average 50 days, Bader, ) corresponds much better than ocean currents with known viability of fragments in the water column; however, seeds and fragments desiccate quickly out of water (Pan et al, ), dramatically decreasing the likely number of viable propagules arriving in Chile. If the minimum probability of introduction is 1 in every 187 ships, then in the last 35 years where 46,340 ships have departed Port Phillip Bay for international ports, we would have expected to see approximately 248 further introductions worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…However, seagrass may have been transported on ships via ballast (in rocks or sand), as mattress material or in anchor wells. Shipping time from SE Australia to Chile (average 50 days, Bader, ) corresponds much better than ocean currents with known viability of fragments in the water column; however, seeds and fragments desiccate quickly out of water (Pan et al, ), dramatically decreasing the likely number of viable propagules arriving in Chile. If the minimum probability of introduction is 1 in every 187 ships, then in the last 35 years where 46,340 ships have departed Port Phillip Bay for international ports, we would have expected to see approximately 248 further introductions worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Manual collection may result in fewer vegetative shoots than mechanical collection (Marion & Orth ), which may explain the significant difference in seed yield. The shore‐based method requires transporting the harvested reproductive shoots from the collecting site to the culturing site, which may result in desiccation (Pan et al ) and overheating of the harvested reproductive shoots and increased embryo mortality, thus further increasing cost. In contrast, the suspended in situ method avoided all of these shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…The shore-based method requires Data are not transformed, and the assumption of homogeneity of variance meets Levene's test (p = 0.301). transporting the harvested reproductive shoots from the collecting site to the culturing site, which may result in desiccation (Pan et al 2012) and overheating of the harvested reproductive shoots and increased embryo mortality, thus further increasing cost. In contrast, the suspended in situ method avoided all of these shortcomings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of seagrass seeds are suggested to be desiccation sensitive, although little is known about the seed ecology of these species. Pan et al (2012) suggested that Zostera marina seeds are very strongly desiccation sensitive which lose vigor completely after desiccating for 24 h. Cho and Sanders (2009) reported that desiccation greatly reduced the viability of R. maritima seeds; the seed viability (35.7%) in dry conditions under ambient temperature (15–25°C) for 10 months was significantly lower than those (>90%) of freshly matured seeds with soft or fully formed seed coats.…”
Section: Introductionmentioning
confidence: 99%